William Shakespeare - Shakespeare, William 1564-1616.; Kastan, David Scott; Kastan, Marina; Harrington, Glenn (New York Sterling Pub., 2000)
Introduces the poetry of William Shakespeare through a sampling of sonnets and excerpts from his plays.
Keywords: Children's poetry, English; English poetry